Comparison of blood glucose in obese and non-obese students in a medical college - Chaudhari, Aparna; Gujarathi, Shreya; Bhatia, Geeta (International Journal of Research in Medical Sciences, 2020)
Background: Obesity has a negative effect on health, leading to reduced life expectancy and/or increased health problems. It is one of the underlying causes of non-communicable chronic diseases like type II diabetes, stroke etc. The study was aimed to compare blood glucose levels in obese and non-obese students in a medical college and to show that obese students are more prone to develop type II diabetes. Methods: A total 20 obese subjects with age and sex matched 20 non-obese subjects were chosen. Their venous blood samples were collected after 12 hours of fasting and analysed for fasting blood sugar (FBS) and haemoglobin A1c (HbA1c). Result: Results of the study showed that obese students have significant (p<0.001) high blood glucose and HbA1c levels as compared to non-obese students. Conclusion: The obese students are prone to develop type II diabetes due to changes in body metabolism as a result of change in fat distribution.